Acute Intestinal Obstruction Due to Ascaris - Bhatt, Pashupati N (Med Phoenix, 2017)
Ascaris lumbricoids is the most common helminthes in tropical areas of developing countries around the world. Intestinal obstruction due to A. lumbricoids is a well known and serious complication in children. We report a case of six yrs female child with intestinal obstruction, who underwent laparotomy and enterotomy to remove the worm masses. Early diagnosis and surgery prevented complications and saved the life of patient. MED Phoenix Volume (1), Issue (1) July 2016, page: 39-40